PEMANFAATAN TEKNOLOGI UNTUK MENDUKUNG KESEJAHTERAAN KELUARGA DENGAN BERWIRAUSAHA - Julian Maradina; Yunita Kurnia Shanti; Luh Nadi; Susi Sih Kusumawardhany; Riska Damayanti (S1 Accounting Program, Universitas Pamulang, 2019)
The development of technological growth at this time has been developing rapidly, one of which is the emergence of fintech. Fintech is a developing innovation in adaptation in computer networks that is applied in the financial sector.The obstacles that occur when utilizing technology are the maximum lack of use of technology for entrepreneurship and also the lack of knowing the technology itself. In this case, many entrepreneurs including housewives who do not understand the application and knowledge of technology. So this Community Service is aimed at providing understanding to Housewives about the use of technology as an instrument for entrepreneurship by utilizing sophisticated technology and to be able to improve towards a prosperous family. In Community Service the method used in the delivery of material is to present the material and question and answer session. And the results obtained in Community Service are housewives who know and understand the use of technology to support family welfare by being open to entrepreneurship and understanding of technological advances can lick up housewives in entrepreneurship. The conclusion from the Community Service activities this time is that there are many benefits in technology, especially in entrepreneurship. Suggestions, it is hoped that this Community Service activity will be sustainable and broader in scope. Keywords: Technology; Fintech; Entrepreneurship